Antioxidant restriction and oxidative stress in short-duration exhaustive exercise - Watson, T. A.; Callister, R.; Taylor, R. D.; Sibbritt, D. W.; MacDonald-Wicks, L. K.; Garg, M. L. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To determine the effect of dietary antioxidant restriction on oxidative stress, antioxidant defenses, and exercise performance in athletes. Oxidative stress has been shown to increase during exercise. To alleviate oxidative stress, a high intake of antioxidant rich foods or supplements may be required in trained athletes. Methods: Plasma oxidative stress and antioxidant defenses were examined in 17 trained athletes who underwent two separate exercise tests. Before the initial exercise test participants followed their habitual (high) antioxidant (H-AO) diets. Then they followed a 2-wk restricted-antioxidant (R-AO) diet before the second exercise test. Blood was taken at rest, after submaximal and high-intensity exhaustive exercise, and after 1 h of recovery. Results: The R-AO diet induced a threefold reduction in antioxidant intake when compared with habitual-antioxidant (H-AO) diets. F2-isoprostane concentration (marker of oxidative stress) was significantly higher after submaximal exercise (38%), exhaustion (45%), and 1 h of recovery (31%) when following the R-AO diet compared with the H-AO diet. Rate of perceived exertion was increased on the R-AO diet whilst exercise time to exhaustion was not affected. Total antioxidant capacity and circulating antioxidant concentrations, although not significantly different, tended to be lower when following the R-AO diet. Conclusion: Athletes regularly participating in up to 40 min of acute high-intensity exercise may require higher intakes of exogenous antioxidants to defend against increased oxidative stress during exercise, which can be met through an adequate intake of high-antioxidant foods. Thus, there seems no valid reason to recommend antioxidant supplements to athletes participating in acute high-intensity exercise events up to 40 min in duration, except in those known to be consuming a low-antioxidant diet for prolonged periods.